Influence of propionic and butyric acids on lipid peroxidation in rat brain and liver homogenates - Yatskevich, Elizaveta V.; Jawad, Marianne; Fedorovich, Sergei V. (Experimental Biology and Biotechnology, 2023)
Gut microbiota can contribute to pathogenesis of different brain diseases. It is believed that strains which produced propionic acid have neurotoxic influence. Also strains which produced butyric acid have neuroprotective influence. In present paper we compare effects of propionic and butyric acids in concentration 1–10 mmol/L on basal level of lipid peroxydation and lipid peroxidation in case of oxidative stress induced by hydrogen peroxide in brain and liver homogenates. Propionic acid does not influence basal level of lipid peroxidation in brain homogenate and inhibits it in liver homogenate. Butyric acid induced this process in liver and brain homogenates. Effect was more pronounced in liver homogenate. Already 1 mmol/L of butyrate increase lipid peroxidation in 2.35 folds in this tissue. Propionic acid in concentration 10 mmol/L leads to increase lipid peroxidation induced by hydrogen peroxide in brain homogenate. The same compounds in concentration 1 and 10 mmol/L to increase lipid peroxidation in case of oxidative stress induced by hydrogen peroxide in liver homogenate. Butyric acid in concentration 5 mmol/L leads to small increase of the same characteristic in brain homogenate, 10 mmol/L of butyrate decreases lipid peroxidation induced by hydrogen peroxide in liver homogenate. Therefore, propionic and butyric acids able to influenced lipid peroxidation in brain and liver homogenates. Propionic acid mainly has antioxidant properties. Butyric acid has prooxidant properties. All effects were more pronounced in liver homogenate.
Keywords: microbiota; propionic acid; butyric acid; brain; lipid peroxidation; reactive oxygen species